2016
DOI: 10.3390/catal6090147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Catalytic Hydrogenation Activity of New N-Acyl-Benzotriazole Rh(I) and Ru(III) Complexes in [bmim][BF4]

Abstract: Abstract:The hydrogenation activity of new N-acyl-benzotriazole Rh(I) and Ru(III) complexes in ionic liquid media is reported in this study. Both complexes were completely soluble in 1-butyl-3-methylimidazolium tetrafluoroborate, [bmim][BF 4 ], and they were able to catalyze the hydrogenation of styrene and 1-octene. While ethylbenzene conversion in styrene hydrogenation reached 84% when the Ru complex was used, 100% conversion was obtained with the Rh complex at 393 K in 6 h. Additionally, total conversion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…On the other hand, the negative effect of DMSO solvent, which is more polar and expected to display better solubility, may be assigned to its enhanced coordination ability to the metal center. This has the potential to block olefin coordination, consistent with the observed diminished catalytic activities . On the contrary, a change in the solvent system did not significantly influence the regioselectivity of the catalyst, affording between 54%–60% of the linear esters across the board.…”
Section: Resultssupporting
confidence: 64%
“…On the other hand, the negative effect of DMSO solvent, which is more polar and expected to display better solubility, may be assigned to its enhanced coordination ability to the metal center. This has the potential to block olefin coordination, consistent with the observed diminished catalytic activities . On the contrary, a change in the solvent system did not significantly influence the regioselectivity of the catalyst, affording between 54%–60% of the linear esters across the board.…”
Section: Resultssupporting
confidence: 64%
“…This trend is supported by the findings that catalytic activities in methoxycarbonylation reactions are controlled by the dielectric constants of the solvents employed [51]. Indeed, a mixture of the dimethyl formamide (DMF)/methanol solvent system afforded no catalytic activity due to a far much higher dielectric constant [52] in addition to the strong coordinating ability of DMF [53].…”
Section: The Effect Of Reaction Conditions On Methoxycarbonylation Rementioning
confidence: 78%
“…It was found that the Rh complex in particular retained its activity for at least 10 cycles when the recyclability of catalysts was examined. 127…”
Section: N -Acylbenzotriazoles As Catalysts and Ligands­mentioning
confidence: 99%